Evaluation of the Potential for Acid Mine Drainage Formation From Pit Lake Walls and its Interaction with the Aquifer System - Diyah Ayu Purwaningsih; I W Redana; Kadek Diana Harmayani; Ni Nyoman Pujianiki (Postgraduate, University of Mataram, 2025)
Pit lakes are water bodies that gradually accumulate in former open-pit mine excavations once mining operations have ceased, typically filled by rainfall, surface runoff, or infiltration from groundwater. Their existence can pose environmental challenges, particularly the development of “acid mine drainage (AMD)”, which is often indicated by low pH values and elevated levels of dissolved metals. This research focuses on evaluating the geochemical properties of pit wall rocks and the water quality within pit lakes in the Separi coal mining region of East Kalimantan. The objective is to determine the likelihood of AMD generation and assess whether contaminants may migrate into the surrounding groundwater system. Field sampling involved collecting materials from pit wall rock, water within the pit lake, adjacent surface water, and groundwater monitoring wells. Mineralogical analysis was performed using X-Ray Diffraction (XRD), while elemental composition was identified through X-Ray Fluorescence (XRF). Water quality parameters such as pH, total dissolved solids (TDS), electrical conductivity, and concentrations of metals—specifically iron (Fe) and manganese (Mn)—were measured using Atomic Absorption Spectroscopy (AAS) and ion chromatography techniques. The findings reveal that several rock samples fall into the Potentially Acid Forming (PAF) category, attributed to their low acid-neutralizing capacity and elevated sulfur content, especially in samples containing pyrite. The pit lake water was found to be acidic (pH 4.2–4.6), with high levels of Fe and Mn, suggesting active sulfide oxidation. Conversely, groundwater from nearby areas displayed more neutral pH values (5.4–6.4) and lower metal concentrations, although some locations still showed contamination risks. These results underscore the need for a comprehensive understanding of geochemical processes and highlight the importance of preventive strategies, such as isolating reactive materials, managing hydrological inputs, and consistently monitoring water quality for long-term environmental protection